Translation of Basic Terms in Cognitive Linguistics -Applied Studied - miad, mustapha; djemai., aicha (El Omda in Linguistics and Discourse Analysis, 2025)
adopted by Arab researchers in their translations. While this diversity reflects the vibrancy of linguistic research in the Arab world, it also poses an obstacle to effective scientific communication and leads to the fragmentation of research efforts